2009
DOI: 10.1007/s00148-008-0229-0
|View full text |Cite
|
Sign up to set email alerts
|

The intra-firm gender wage gap: a new view on wage differentials based on linked employer–employee data

Abstract: Gender wage gap, Linked employer–employee data, Labor relations, J16, J31,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
62
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(73 citation statements)
references
References 40 publications
8
62
0
3
Order By: Relevance
“…This result has also been found by Gartner and Stefan (2004) as well as Heinze and Wolf (2010). To the best of our knowledge there is just one study that also uses individual data over time.…”
Section: Introductionsupporting
confidence: 83%
“…This result has also been found by Gartner and Stefan (2004) as well as Heinze and Wolf (2010). To the best of our knowledge there is just one study that also uses individual data over time.…”
Section: Introductionsupporting
confidence: 83%
“…Bell (2005) found that firm size and the disproportionately small number of female CEOs and company chairwomen were responsible for between 50 and 60% of the gender pay gap. Heinze and Wolf (2010) also reported that the gender pay gap was wider in large German concerns, at the variable is denoted by "FIRMSIZE" and is calculated as the logarithm of the firm's total assets. It is expected to be positive, as the gender pay gap among directors will be greater the larger the firm.…”
mentioning
confidence: 99%
“…potential experience (linearly and squared), tenure (linearly and squared), a dummy for non-German nationality, a group of six education dummies, 10 and a group of nine occupation dummies. 11 Next, we include several plant characteristics found to matter for unexplained pay gaps in earlier studies using the LIAB data (cf., e.g., Achatz et al 2005;Heinze and Wolf 2010;Beblo et al 2011): the log of establishment size, 12 a dummy for works council existence, two dummies for the presence of a collective agreement either at the sector or the firm level, dummies for exporting activity, foreign ownership, plant location in a rural area, and new production technology, both the shares of women and qualified workers in the plant's workforce, and eight sector dummies. 13 Controlling for these individual and plant characteristics is meant to account for productivity differences, segregation effects, and institutional as well as organisational factors likely to influence the gender pay gap.…”
Section: Resultsmentioning
confidence: 99%